Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/polym13244461
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels Based on Alginates and Carboxymethyl Cellulose with Modulated Drug Release—An Experimental and Theoretical Study

Abstract: New hydrogels films crosslinked with epichlorohydrin were prepared based on alginates and carboxymethyl cellulose with properties that recommend them as potential drug delivery systems (e.g., biocompatibility, low toxicity, non-immunogenicity, hemostatic activity and the ability to absorb large amounts of water). The characterization of their structural, morphological, swelling capacity, loading/release and drug efficiency traits proved that these new hydrogels are promising materials for controlled drug deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…In line with previous research, Peptu et al [ 80 ] synthesized alginate (AG)/CMCNa-based hydrogel with ECH as a crosslinking agent. It was found that high superabsorbent properties, indicated by a maximum swelling ratio of 1273%, were observed for the sample with 1:1 AG:CMC molar ratio, 6.6% polymer concentration, and 0.75 mL of ECH.…”
Section: Types Of Crosslinking Agents In the Synthesis Of Cellulose-b...supporting
confidence: 59%
“…In line with previous research, Peptu et al [ 80 ] synthesized alginate (AG)/CMCNa-based hydrogel with ECH as a crosslinking agent. It was found that high superabsorbent properties, indicated by a maximum swelling ratio of 1273%, were observed for the sample with 1:1 AG:CMC molar ratio, 6.6% polymer concentration, and 0.75 mL of ECH.…”
Section: Types Of Crosslinking Agents In the Synthesis Of Cellulose-b...supporting
confidence: 59%
“…Thus, if the hydrodynamic scenario allows the “decoding” of some drug release mechanisms, then the Schrodinger scenario can be employed for the “plotting” of the drug release curves. For a better understanding of our argumentation, let us remind the hypotheses from (Peptu et al, 2021 ): the dynamics of any complex system, independent of the two scale resolutions (differentiable and non-differentiable scale resolutions), are one-dimensional dynamics; the synchronization of the dynamics of any complex system at the two scale resolutions is achieved by “compensating” the velocity fields and given by the restriction ; the polymer network operates by means of a potential vector (for details, see (Peptu et al, 2021 )). …”
Section: Resultsmentioning
confidence: 99%
“…The functionality of such a hypothesis implies, based on the Scale Relativity Theory, employing, in the description of polymer-drug dynamics, continuous and non-differential curves (fractal/multifractal curves). Then, two scenarios for describing polymer-drug dynamics become compatible: release dynamics in the Schrödinger multifractal scenario (multifractal Schrödinger equation) (Peptu et al, 2021 ): release dynamics in the Madelung multifractal scenario (multifractal hydrodynamic equation) (Peptu et al, 2021 ): where denotes the multifractal specific potential: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug delivery vector is one of the most common applications of CMC gels owing to their good drug loading and drug release ability [ 43 , 44 , 45 , 46 , 47 ]. Zhang et al designed a type of CMC gel, CMC-polydopamine-NaI (CDI) hydrogel, with the anti-tumor abilities of photothermal therapy (PTT) and photodynamic therapy (PDT) after loading polydopamine (PDA) and Chlorin e6 (Ce6) [ 48 ].…”
Section: Applicationsmentioning
confidence: 99%